Asesmen Kompetensi Minimum Ditinjau Secara Filsafat Pendidikan - Ahmad Isnaini (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2021)
Minimum Competency Assessment (AKM) is one of the improvements on the learning evaluation provided by the government so far. The AKM is implemented to measure the literacy and numeracy abilities of Indonesia students, due to the low achievement of the Program for International Student Assessment (PISA) and Trends in International Mathematics and Science Study (TIMSS). This article is a literature study discussing AKM from the Educational Philosophy point of view, concerning the Ontology, Epistemology, and Axiology of the AKM. The study concludes that AKM is feasible to implement for improving the literacy and numeracy of students in Indonesia.